RETRACTED: Analyzing the Role of Corporate Social Responsibility for Sustainable Environmental Performance: Mediating Roles of Environmental Strategy and Environmental Outcomes - Wang, Xiaodong; Bian, Weijun (Frontiers in Psychology, 2022)
This study examines the relationship between corporate social responsibility (CSR) and environmental performance, utilizing data from 415 small and medium-sized enterprises (SMEs) in China as a case study. We found that CSR has a direct and significant impact on environmental performance (EP) and is positively correlated to environmental strategy (ES) and environmental outcomes (EO), both of which improve environmental performance, i.e., they serve as a significant mediating factor between CSR and environmental performance. Our study will help general managers and policy maker of SMEs, provides a beneficial model for managing CSR, ES, and EO to achieve sustainable environmental performance. Specifically, it can assist general managers of SMEs in strengthening their internal resources such as CSR, ES, and EO in order to improve long-term environmental performance.